Progress in Understanding Postnatal Immune Dysregulation in Allergic Disease - Susan L. Prescott, MD, PhD (World Allergy Organization Journal, 2010)
It is increasingly unlikely that allergic disease is the result of isolated immune defects, but rather the result of altered gene activation patterns in intricate immune networks. This appears to be driven by complex environmental changes, including microbial exposure, diet, and pollutants, which are known to modify immune development in early life, beginning in pregnancy. The first models showing possible epigenetic mechanisms for these effects are beginning to emerge. This review focuses on recent advances in our knowledge of the consequent effects on postnatal immune development, highlighting recognized differences in children with and without allergies. Although we characterized essential differences in longitudinal T-cell development more than 10 years ago, new technologies using whole genome microarrays are now being used to examine for differential gene expression in T cells from individuals with allergies. We have also recently performed the first comprehensive study of the longitudinal development of innate toll-like receptor responses in children with and without allergies during the first 5 years of life, identifying significant differences in these pathways as well. Finally, although there are preliminary differences in regulatory T-cell function at birth, longitudinal studies are limited by difficulties isolating these cells in sufficient numbers from young children for functional studies. Thymic tissue isolated during cardiac surgery is a rich source of regulatory T-cell function in children and may provide further avenues for assessing differences in maturation of these cells in individuals with allergies. To further understand the pathogenesis of these altered patterns of immune response, future research needs to encompass the complexity of gene-environmental interactions, which confer individual susceptibility to environmental exposures. Keywords: postnatal immune development, epigenetic mechanisms, children with and without allergies